PERSONAL PRONOUNS OF SASAK LANGUAGE: DESCRIPTIVE STUDY IN “PUJUT” DIALECT AT BILELANDO IN CENTRAL LOMBOK IN 2021/2022 - Masyudi (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to canvass views of Sasak personal pronouns used in ‘Pujut’ dialect at Bilelando in 2021\2022. Hence, the significance of this study is linguistics, and cross cultural. It attempts to describe and investigate about forms, types, and distributions of the personal pronouns based on the native’s daily conversations and behaviors. This project applies random sampling technique to take both informants from Bilelando village. The data are collected through observation, note taking, and documentary technique, complemented with qualitative interviews to native speakers of Sasak in ‘Pujut’ dialect, whereas the interviews have provided information that has been organized in supporting and developing themes. The data collected would be qualitative forms and analyzed descriptively. The results show that there are six forms and three types of Sasak personal pronouns in ‘Pujut’ dialect at Bilelando in 2020/2021. in which can be distributed before or after a word or phrase. They even can be distributed as enclitic of a word.